Head and Neck and Endocrine Surgery From Clinical Presentation to Treatment Success - Sakr, Mahmoud (Springer International Publishing : Imprint: Springer, 2016)
This book addresses a wide range of topics relating to head and neck and endocrine surgery, including: maxillofacial injuries, surgery of the scalp, surgery of the salivary glands, jaw tumors, surgery of the oral cavity (lips, tongue, floor of the mouth, and palate), swellings and ulcers of the face, inflammation in the neck, cervical lymphadenopathy, midline and lateral neck swellings, tumors of the pharynx, and endocrine surgery (thyroid gland, parathyroid glands, suprarenal glands, and neuroendocrine tumors). The aim is to clearly describe and illustrate how to diagnose and treat diverse conditions in accordance with evidence-based practice. The coverage thus extends beyond surgical indications and procedures to encompass aspects such as anatomy, clinical presentation, and imaging diagnosis. The book has been structured in such a way as to facilitate quick reference. While it is primarily intended for practitioners, it will also be suitable for upper graduate students.